Conceptual understanding, career aspiration, self-efficacy and experience of third-year chemistry students - Dagogo, Ibiye Tonye (Department of Chemistry, 2020)
The retention of science students in universities has become a concern over the recent years, globally and in South Africa. Literature reveals that students’ retention is affected by aspects such as conceptual understanding, career aspiration, self-efficacy and experience; which were considered independently and not holistically. This study aims to understand the persistence of chemistry students at the University of Cape Town in South Africa, by bringing together different factors such as conceptual understanding, career aspiration, self-efficacy and experience in chemistry. The aim was achieved by adopting a qualitative case study approach that focused on students from the Extended Degree Programme (EDP) and Mainstream (MS) courses. Bandura’s Social Cognitive Theory and Lent, Brown and Hackett’s Social Cognitive Career Theory were used as the theoretical frameworks for the research. The sample consisted of 28 students of diverse ethnicity and gender from EDP and MS, who were enrolled in a third-year chemistry course. Data were collected from documents, questionnaires and interviews. Although this study was mainly qualitative, some quantitative data were generated from the analysis of the documents. The qualitative data from the questionnaires and interviews were subjected to inductive thematic analysis, which allows the themes to emerge from the study without applying a pre-existing coding scheme. My original contribution to knowledge as it relates to students’ persistence is that persistence depends on a number of inter-related factors, which are different for individual students. The study reveals that there was no relationship between academic performance and either career aspiration or self-efficacy for the cohort. This finding means that students may continue to perform well in a course even if they do not have an aspiration or a particular career in mind. Strong career aspiration and sense of self-efficacy may not necessarily result in good academic performance. Students’ persistence in a study programme may be driven largely by other aspects such as personal goals and responsibilities, which obtaining a university degree may help them to achieve. The majority of EDP students persisted because they wanted to provide financial help for their family, whereas the majority of MS students did not want the money spent on their education by their parents to be wasted. This finding highlights the strong role that outcome expectation played in students’ persistence. The findings also revealed that some of the students have well-defined, but probably not always realistic ideas of a desirable career. For the majority of the students, chemistry was a second-choice option, and they did not have a career aspiration for chemistry; however, their career aspirations changed during their course of study. The Science Faculty requirement for Page | iii a second major was a strong contextual factor that had a significant influence on students’ choice of chemistry. EDP students possessed a strong sense of self-efficacy that was expressed verbally, while MS students possessed a strong sense of self-efficacy that was tacit. In terms of experience in chemistry, all students had a disheartening experience at different stages in their studies; however, the study revealed that EDP students found the transition to second-year difficult, whereas MS students experienced difficulty with the transition to third-year. Another significant aspect of their experience is that all students found support mechanisms, especially from friends and family that helped them to persist. Other aspects of course design such as the change in structure in terms of the number of tutorials in EDP and MS as well as the faster pace in second-year chemistry were also problematic for the majority of EDP students. In conclusion, although the syllabus for the two programmes (EDP and MS) is the same, the study revealed that the learning experiences of the students in these programmes differed. An interesting finding that emerged, from this study, is the positive correlation between students National Benchmark Tests for mathematics and their third-year chemistry scores. This finding suggests the possibility of exploring the option of using scores from the National Benchmark Tests as part of the admission requirements in the Science Faculty. Based on the findings from this study, the Science Faculty should provide adequate counselling to steer students on study paths within the Bachelor of Science degree that may help them to achieve their initial career preferences; and open their eyes to various opportunities. The Department of Chemistry should seek to revise the curriculum for both EDP and MS courses to minimise the stress related to the transition between the different years of the Bachelor of Science degree.